2020
DOI: 10.1002/hon.2759
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for high‐dose methotrexate associated acute kidney injury in patients with hematological malignancies

Abstract: High dose methotrexate (HDMTX)-induced acute kidney injury (AKI) is a well-known adverse event in hemato-oncology patients. Our purpose was to define factors and setup cutoffs that may help better identify patients at-risk for developing AKI following HDMTX. All consecutive patients who received MTX dose ≥1 g were retrospectively reviewed. We compared patients with or without renal toxicity. We used a logistic regression model to define baseline variables associated with AKI. Overall survival (OS) was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 29 publications
0
33
3
Order By: Relevance
“…It is plausible that the risk of AKI when HDMTX is administered on day 1 of (R)CHOP is higher especially during the first treatment cycle when other risk factors for AKI (for example tumor lysis syndrome) or factors associated with higher risk for HDMTX-related nephrotoxicity (for example hypoalbuminemia) are more likely to be present. 29,30 Not only did patients in our HDMTX-P cohort receive more HDMTX cycles during the first treatment cycle (55% vs <40%), but they also received more HDMTX-containing cycles/patient overall. The definition of AKI was also different between the studies; we defined grade 2 AKI as creatinine increase >1.5-3.0 times the upper limit of normal per CTCAE V5.0 whereas Wilson et al defined it as creatinine 2-2.9 times baseline per KDIGO criteria.…”
Section: Discussionmentioning
confidence: 93%
“…It is plausible that the risk of AKI when HDMTX is administered on day 1 of (R)CHOP is higher especially during the first treatment cycle when other risk factors for AKI (for example tumor lysis syndrome) or factors associated with higher risk for HDMTX-related nephrotoxicity (for example hypoalbuminemia) are more likely to be present. 29,30 Not only did patients in our HDMTX-P cohort receive more HDMTX cycles during the first treatment cycle (55% vs <40%), but they also received more HDMTX-containing cycles/patient overall. The definition of AKI was also different between the studies; we defined grade 2 AKI as creatinine increase >1.5-3.0 times the upper limit of normal per CTCAE V5.0 whereas Wilson et al defined it as creatinine 2-2.9 times baseline per KDIGO criteria.…”
Section: Discussionmentioning
confidence: 93%
“…Some earlier studies have suggested the association of HMN or delayed MTX clearance with hypoalbuminemia. 7,16,19 While another study found low baseline serum protein and not low albumin levels as risk factor for HMN. 4 The cutoffs for low serum albumin were diverse (Supporting Information Table S1), and none of the study monitored CRP along with serum albumin, which may lead to falsely low albumin levels.…”
Section: Discussionmentioning
confidence: 96%
“…These studies are retrospective and heterogeneous with varying use of supportive measures. 4,7,8 Therefore, we decided to study factors affecting HMN prospectively in a center where serial MTX monitoring as per protocol is not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Simpler geriatric assessment tools have been developed to predict outcomes in NHL. An association of Charlson Comorbidity Index with risk of methotrexate (MTX)‐induced kidney injury in univariate analysis 34 and with OS has been demonstrated in a National Cancer Database US‐based study 35 …”
Section: Role Of Geriatric Assessment In Elderly Pcnslmentioning
confidence: 99%
“…The PRIMAIN study evaluated R-MP in PCNSL patients >65 years. PRIMAIN is the largest prospective study specifically designed for elderly PCNSL patients, reporting one-and two-year PFS rates of 46Á3% (95% CI 36-55) and 37Á3% (95% CI [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and OS rates of 56Á7% (95% CI 47-66) and 47% (95% CI 37-56) respectively. TRM rate was 8Á4% and 81Á3% of the patients experienced adverse events ≥grade 3.…”
Section: Treatment Of the 'Fit' Elderly With Dose-adapted Hd-mtx-base...mentioning
confidence: 99%